Laboratory breeding of lymnaea natalensis (krauss, 1848), intermediate host of fasciola gigantica (cobbold, 1856) (2013)
Lymnaea natalensis the intermediate host of the Fasciola gigantica (the causative agent of liver fluke disease) was collected from the zoological and botanical gardens, University of Ibadan, Nigeria and reared in our laboratory. The aim was to improve and standardize a rearing and maintenance technique for this snail. Two kinds of diets were compared: Blanched, Dried lettuce (A) and blanched, dried lettuce + 10% Calcium carbonate (CaCO3) (B). The age at oviposition, growth rate using shell size as indices and the durations of incubation and hatching were determined. Age at beginning of ovipostion ranged from 39 to 60 days. The snails fed with CaCO3 enhanced diet presented an increased growth rate, however, the difference was not significantly different (p>0.05). The maximum size attained by snails fed with diet A was 18mm length and 8mm height and 23mm length and 14mm height for diet B. The maximum duration of incubation of the eggs for the diets are 12 days (B) and 11 days (A) while the duration of hatching for diet B and A are minimum of 2 days and 6 days respectively. The method of mass breeding and maintenance of Lymnaea natalensis using CaCO3 as supplement to blanched dried lettuce was found to be suitable in our laboratory